Examining the Impact of Demographics, Travel Patterns, and Awareness on Sustainable Tourism and Cultural Preservation in Coastal Karnataka - SAILESH, Bhaskar; NAYANI, Nagarjun (Journal of Environmental Management and Tourism; Vol 16 No 3 (2025): JEMT, Volume XVI, Issue 3(79), Fall 2025, 2025)
This study explores the influence of demographic factors, travel patterns, and knowledge on sustainable tourism practices and cultural preservation in coastal Karnataka. The research examines how variables such as age, income, education, and gender shape tourists' engagement in environmentally responsible behaviours and their support for cultural conservation initiatives. The findings highlight those younger tourists, particularly from Generation Z, exhibit stronger preferences for sustainable practices, while higher income groups are more likely to afford eco-friendly options. Additionally, educational background and gender differences contribute significantly to varying levels of awareness and participation in sustainable tourism. The study also underscores the importance of community-based tourism (CBT) in fostering both environmental and cultural preservation, with a particular emphasis on the role of local communities and tourists in these efforts. The implications of these findings are valuable for developing targeted strategies to promote sustainable tourism and enhance the preservation of coastal heritage. These results offer important insights for policymakers and tourism stakeholders seeking to create more inclusive and effective approaches to sustainable tourism development.